Transcriptional regulation of metabotropic glutamate receptor 2/3 expression by the NF-κB pathway in primary dorsal root ganglia neurons: a possible mechanism for the analgesic effect of L-acetylcarnitine - Nicoletti Ferdinando; Morales Maria Elena P; De Petris Laura; Copani Agata; Chiechio Santina; Gereau Robert W (SAGE Publishing, 2006)
Abstract L-acetylcarnitine (LAC), a drug utilized for the treatment of neuropathic pain in humans, has been shown to induce analgesia in rodents by up-regulating the expression of metabotropic glutamate receptor 2 (mGlu2) in dorsal root ganglia (DRG). We now report that LAC-induced upregulation of mGlu2 expression in DRG cultures involves transcriptional activation mediated by nuclear factor-kappaB (NF-κB). A single application of LAC (250 μM) to DRG cultures induced a transient increase in mGlu2 mRNA, which was observable after 1 hour and was no longer detectable after 1 to 4 days. In contrast, LAC treatment had no effect on mGlu3 mRNA expression. Pharmacological inhibition of NF-κB binding to DNA by caffeic acid phenethyl ester (CAPE) (2.5 μg/ml for 30 minutes) reduced the constitutive expression of mGlu2 and mGlu3 mRNA after 1-4 days and reduced the constitutive expression of mGlu2/3 protein at 4 days. This evidence combined with the expression of p65/RelA and c-Rel in DRG neurons indicated that expression of mGlu2 and mGlu3 is endogenously regulated by the NF-κB family of transcription factors. Consistent with this idea, the transient increase in mGlu2 mRNA induced by LAC after 1 hour was completely suppressed by CAPE. Furthermore, LAC induced an increase in the acetylation of p65/RelA, a process that enhances the transcriptional activity of p65/RelA. These results are consistent with the hypothesis that LAC selectively induces the expression of mGlu2 by acting as a donor of acetyl groups, thus enhancing the activity of the NF-κB family of transcription factors. Accordingly, we show that carnitine, which has no effect on pain thresholds, had no effect on p65/RelA acetylation and did not enhance mGlu2 expression. Taken together, these results demonstrate that expression of mGlu2 and mGlu3 mRNA is regulated by the NF-κB transcriptional machinery, and that agents that increase acetylation and activation of NF-κB transcription factors might induce analgesia via upregulation of mGlu2 in DRG neurons.